Theatrical Intervention as a Pathway to Moral Virtue Development - Wang, Lijuan; Mower, Deborah; Garvey, Margaret (My University, 2015)
Moral virtue development is grounded in social relationships that foster the socioemotional intelligence underlying moral virtue. Recent research shows a decrease in socioemotional intelligence with implications for moral virtue development. This project is a feasibility study of a theatrical intervention with parent-child dyads to increase socioemotional intelligence and proto-virtuous character by improving parent-child mutual responsiveness. Our theatrical approach combines direct development of mutual responsiveness and practice of moral virtue scripts, providing a powerful and seamless integration of philosophy, theatre art and social science (longitudinal experimental design, measurement, educational intervention, statistical analyses).
Keywords: Philosophy; Psychology, Developmental.; Theater.